SAT0129 ROLE OF SHARED EPITOPE ON THE EFFECTIVENESS OF TNFI TREATMENT FOR PATIENTS WITH RHEUMATOID ARTHRITIS. (2nd June 2020) - Zhuo, J.; Bryson, J.; Xia, Q.; Sharma, N.; Samal, C.; Lama, S.; Weinblatt, M. E.; Shadick, N.
Abstract : Background: Rheumatoid arthritis (RA) has been shown a strong genetic association with particular HLA–DRB1 alleles containing shared epitope (SE). However, whether SE is clinically useful in treatment choices is insufficiently investigated 1 and previous studies have presented mixed findings in the role of SE in the response of TNFi therapies 2, 3 . Objectives: To assess the role of SE in response to TNFi treatment in real-world RA patients (pts). Methods: Pts enrolled in a large RA registry, Brigham and Women's Hospital RA Sequential Study, with known SE and received TNFi therapies were included for the analysis. TNFi pts were identified by the first-time use of the drugs between March 2003 to June 2018. For this analysis, all pts were followed up to 1 year. Summary statistics are reported for demographics, serostatus and disease activity (DA) at baseline and follow-up, stratified by SE status. Given the strong association of SE and anti-citrullinated protein antibody (ACPA), the analysis was further stratified by ACPA status. The effect of SE on change in DA was assessed using linear regression model with age, gender, RA disease duration, baseline DA, smoking status, SE, ACPA and ACPA-SE interaction as covariates. Results: Of the 484 TNFi pts included in the study, 68.8% were SE+. SE+ pts (vs SE-) were more likely to be rheumatoid factor positive, have erosive disease and a higher disease duration, irrespective of ACPA status. No difference in the change of DA was observed by SE. In SE- pts, ACPA+ pts had a greater reduction of DA than ACPA- pts (Table 1 ). After accounting for baseline differences, there was no significant effect of SE status on the mean change from baseline in any of the 3 DA measures.(Figure 1 ) The change in DA was not associated with ACPA but was significantly affected by disease duration and baseline DA. Conclusion: This real-world study validates the finding from previous studies conducted in clinical settings that SE does not differentiate treatment response for TNFi therapies. References: [1]Saruhan-Direskeneli G, et al. Rheumatology (Oxford ) 2007;46(12):1842-44 [2]Skapenko A, et al. Clin Exp Rheumatol 2019;37(5):783-790 [3]Rigby W, et al. Annals of the Rheumatic Diseases 2019;78(2):263-264 Disclosure of Interests: Joe Zhuo Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Joshua Bryson Shareholder of: I own shares of Bristol-Myers Squibb Company, Employee of: I am a paid employee of Bristol-Myers Squibb Company, Qian Xia Shareholder of: I own shares of Bristol-Myers Squibb Company, Employee of: I am a paid employee of Bristol-Myers Squibb Company, Niyati Sharma Consultant of: I work as a consultant for Bristol-Myers Squibb Company, Chidananda Samal Consultant of: I work as a consultant for Bristol-Myers Squibb Company, Sonie Lama Shareholder of: I own shares of Bristol-Myers Squibb Company., Employee of: I am a paid employee of Bristol-Myers Squibb Company., Michael E. Weinblatt Grant/research support from: BMS, Amgen, Lilly, Crescendo and Sonofi-Regeneron, Consultant of: Horizon Therapeutics, Bristol-Myers Squibb, Amgen, Abbvie, Crescendo, Lilly, Pfizer, Roche, Gilead, Nancy Shadick Grant/research support from: Mallinckrodt, BMS, Lilly, Amgen, Crescendo Biosciences, and Sanofi-Regeneron, Consultant of: BMS